The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1001/jamacardio.2020.0652
|View full text |Cite
|
Sign up to set email alerts
|

Off-label Use of Direct Oral Anticoagulants Compared With Warfarin for Left Ventricular Thrombi

Abstract: IMPORTANCE Left ventricular (LV) thrombi can arise in patients with ischemic and nonischemic cardiomyopathies. Anticoagulation is thought to reduce the risk of stroke or systemic embolism (SSE), but there are no high-quality data on the effectiveness of direct oral anticoagulants (DOACs) for this indication.OBJECTIVE To compare the outcomes associated with DOAC use and warfarin use for the treatment of LV thrombi. DESIGN, SETTING, AND PARTICIPANTSA cohort study was performed at 3 tertiary care academic medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
213
4
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(260 citation statements)
references
References 38 publications
8
213
4
4
Order By: Relevance
“…[12,14,24,25] Our results are contrary to those of Robinson et al, who reported that treatment with DOACs was associated with a higher risk of SSE compared to warfarin. [13] It is important to note that in this study, DOAC group had more patients with traditional risk factors of stroke like history of prior SSE, hyperlipidemia, atrial brillation, apical thrombus and pedunculated thrombus which could have contributed to more SSE events. Moreover, due to retrospective nature of this study, there can be some unmeasured confounders leading to increased SSE events in their study.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[12,14,24,25] Our results are contrary to those of Robinson et al, who reported that treatment with DOACs was associated with a higher risk of SSE compared to warfarin. [13] It is important to note that in this study, DOAC group had more patients with traditional risk factors of stroke like history of prior SSE, hyperlipidemia, atrial brillation, apical thrombus and pedunculated thrombus which could have contributed to more SSE events. Moreover, due to retrospective nature of this study, there can be some unmeasured confounders leading to increased SSE events in their study.…”
Section: Discussionmentioning
confidence: 74%
“…[10,11] The effectiveness of DOACs in treating LV thrombus is controversial, with some studies favoring their use and others not. [11][12][13][14] The large scale studies and metanalysis comparing the effectiveness and, safety of the DOACs vs warfarin in treatment of LVT are lacking. Thus, we sought to perform this systematic review and metaanalysis to compare the effectiveness and safety of warfarin vs DOACs for the treatment of LVT.…”
Section: Introductionmentioning
confidence: 99%
“…There have been no randomized trials to our knowledge that have compared dual and triple therapy in patients with LV thrombosis complicated by thromboembolism and STEMI [10,11]. Although data from an observational study have shown an increased risk of systemic thromboembolism with the use of OAC as compared to warfarin, prospective randomized studies are lacking in this area [12]. In our case, due to hemodynamically significant groin hematoma requiring transfusion, the treatment rationale was modified to a limited duration of double therapy (apixaban and clopidogrel) with a follow-up echocardiogram to evaluate the necessity for the continuation of anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the largest multicenter, retrospective study for LVT diagnosed by TTE argues against the assumption of equivalence between DOACs and warfarin. 44 Trials comparing DOACs and warfarin in the treatment of LVT are ongoing in China, Malaysia, and Israel (ClinicalTrials.gov number NCT03764241, NCT02982590, and NCT03232398, respectively).…”
Section: Current Guidelines Recommend Vitamin K Antagonistsmentioning
confidence: 99%